2000
DOI: 10.1007/pl00002349
|View full text |Cite
|
Sign up to set email alerts
|

Remission Rates Following Preoperative Chemotherapy and Radiation Therapy in Patients with Breast Cancer

Abstract: Even though the small number of patients in the present protocol does not permit definite conclusions, the results of combined modality treatment seem promising with regard to tumor remission within the treated breast and as a tool for breast conservation in advanced stage disease. On the basis of these encouraging data a prospective Phase-III study has been initiated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1
2

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 19 publications
0
23
1
2
Order By: Relevance
“…External validity of our study has recently been given indirectly by publication of the results of a non-randomized comparison of neoadjuvant radio-chemotherapy versus neoadjuvant chemotherapy alone [43]. A randomized study has been initiated.…”
Section: Discussionmentioning
confidence: 99%
“…External validity of our study has recently been given indirectly by publication of the results of a non-randomized comparison of neoadjuvant radio-chemotherapy versus neoadjuvant chemotherapy alone [43]. A randomized study has been initiated.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery is performed in every patient without distant metastases irrespective of the primary tumor response as assessed by palpation, ultrasound, or nuclear magnetic resonance. In a small series, we have achieved a histopathologically complete response in 24 out of 56 tumors, which was significantly more than after induction chemotherapy alone [2]. We here present the extended singleinstitution experience with 134 patients who underwent preoperative chemo-/radiotherapy and had a final histopathologic assessment of the tumor response.…”
Section: Introductionmentioning
confidence: 94%
“…In this overview, all types of surgery were included. Based on several randomized clinical trials with follow-up times > 10 years, breast-preserving surgery and subsequent radiotheraphy are regarded as a safe treatment option for stage I and II tumors with respect to local recurrence-free survival and overall survival [2,4,13,19,26,27,34,35]. Postmastectomy radiotherapy has regained interest, and large randomized trials have demonstrated an overall survival benefit [11].…”
Section: Introductionmentioning
confidence: 99%
“…Local hyperthermia was delivered with 43.5-44.5 °C over 60 min immediately before interstitial radiotherapy. Details of treatment have been described previously [1,15,16]. 214 neoadjuvant patients (82/100 patients with cT1-T2 tumors, 84/137 patients with cT3 tumors, and 48/78 patients with cT4 tumors) received only an electron boost after external-beam radiotherapy and no interstitial boost.…”
Section: Interstitial Therapy 101 Patients Received An Interstitial Bmentioning
confidence: 99%